Development of a training module for adolescent Peer Counsellors based on a systematic literature review - Susetyo, Yuli Fajar; Supriyadi, Aliyaturrahmah; Setiyawati, Diana; Hidayati, Nurul Kusuma (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2024)
Adolescence is a critical phase in mental health, with 50% of severe mental disorders found to have an onset in adolescence. To prevent and detect early symptoms of mental disorders, school adolescent peer counseling programs have been formed since the 1970s. Peer counselors’ roles include providing emotional support for their peers through listening, helping as a co-problem solver, and, if needed, referring peers who need professional help to the professionals available at school. This project aims to develop a practical training module for student peer counselors and form a peer counselor program in the Special Region of Yogyakarta. The training module was formed through a systematic literature review of existing scientific literature. The literature results concluded that the main topics of peer counselor training are communication skills, attitudes, other skills, self-development skills, ethics, and focus topics. A training module was developed based on the results of a systematic literature review.